Patients with Liver Cirrhosis as Frequent Attenders of Emergency Departments - Chen-Ju Chuang; Yi-Fang Wu; Kai-Hsiang Wu; Yi-Chuan Chen (Emergency Medicine International)
Objectives. Frequent attendance for nonemergency problems to emergency departments (EDs) contributes to ED overcrowding, resulting in medical care delays, increased medical errors, and social and economic burdens. Most studies regarding frequent attenders of EDs examine general patients without classifying certain subgroups. This study aimed to investigate patients with liver cirrhosis who present repeatedly to the ED. Methods. This was a retrospective, observational cohort study of adult patients with a history of liver cirrhosis presenting to the ED from January 2011 to December 2015. We included patients with cirrhosis whose first ED visit occurred during the study period. We went far back for 20 years and excluded patients with any ED visits (including both cirrhosis and noncirrhosis-related ones) before the study period. We categorized frequent attenders as patients with more than 4 ED visits within 12 months after the first ED visit; infrequent attenders were those who did not meet this criterion. Results. A total of 3513 patients with cirrhosis were included in this retrospective cohort study. Compared with the infrequent attenders, frequent attenders had a higher rate of presentations due to hepatic encephalopathy (15.2% vs 13.7%, P<0.001) and ascites (10% vs 4%, P<0.001). A Kaplan–Meir survival analysis revealed that frequent attendance was not associated with increased mortality during the study period (hazard ratio 1.02, 95% confidence interval 0.92–1.14; P=0.68). Conclusions. Hepatic encephalopathy and ascites account for more ED visits in frequent than in infrequent attenders. Our findings provide information for those planning outpatient support for patients with cirrhosis. Further research is warranted.